Concave Side Apical Control in Early Onset Scoliosis Managed with Growing Rods - Tameem Mohammed Elkhateeb; Mohamed Wafa; Mahmoud Ahmed Ashour (Spine Surgery and Related Research)
Objective: To evaluate curve correctability, complications, and rate of growth following treatment. Background: Distraction-founded techniques such as traditionally growing rods or magnetically controlled growing rods are the almost globally accepted management patterns for early onset scoliosis. However, periodic lengthening operations are still needed. Moreover, an MCGR is difficult to contour, and implant-associated problems are common. We developed concave side apical control of the growing rod in which an additional anchor site is inserted at the apex to enhance stability and assist in the adjustment of axial deformity. Methods: Entirely skeletally immature early onset scoliosis (EOS) cases with a progressive curve of >40° and without bone or soft tissue weakness were appropriate for this study. Coronal Cobb angle, sagittal parameters, complications, spinal length, and reoperations were documented with at least a 3-year follow-up. Results: In this study, 15 patients were involved. The mean age was 7 years. The mean preoperative Cobb angle was 48°, which postoperatively became 12° with the percentage of coronal correction reaching 75.73%. The mean Cobb angle degrees of correction were 39°. T1-S1 height increased by 10 mm/year. Postoperative complications occurred in two cases with single rod technique and rod breakage. Conclusions: The concave side apical control of the growing rod seems to be a hopeful surgical procedure for the management of EOS. Curve correctability in patients was 60% and can be sustained for a minimum of 2 years. Reoperations and complications might not be constricted, but the complication frequency looks more reasonable than in the current systems.